An experimental and numerical study on scaling effects in the low velocity impact response of CFRP laminates. (15th October 2016) - Xu, Z.; Yang, F.; Guan, Z.W.; Cantwell, W.J.
Abstract: Scaling effects in the low velocity impact response of plain weave carbon-fibre-reinforced plastic (CFRP) panels have been investigated both experimentally and numerically. The experimental tests were undertaken using an instrumented drop-weight impact tower and the numerical simulations were conducted using the commercially-available finite element (FE) solver ABAQUS/Explicit. Here a rate-dependent damage model was implemented through the ABAQUS user-defined material interface, VUMAT, to describe the mechanical behaviour of the composite laminates. The experimental tests and numerical simulations both indicate that at energies above the damage threshold, damage does not obey a simple scaling law, becoming more severe as the scale size is increased. An examination of the damaged samples in the tests and numerical simulations indicated that, for a given scaled impact energy, fibre damage, in the form of large cracks extending in the warp and weft directions, was more severe in the larger samples. It is argued that the energy absorbed in fibre fracture scales with the square of the scale factor, i.e. n 2, whereas the initial impact energy scales as n 3 . This discrepancy results in increased levels of energy needing to be absorbed in larger scale sizes, leading to greater levels of impact damage in the larger scale sizes.